2011
DOI: 10.7847/jfp.2011.24.1.001
|View full text |Cite
|
Sign up to set email alerts
|

Genetic positioning of Korean viral hemorrhagic septicemia virus (VHSV) from cultured and wild marine fishes

Abstract: Viral haemorrhagic septicaemia virus (VHSV) is an epidemic virus in olive flounder

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…However, several pathogenic fish viruses have been isolated or detected from wild marine fish in coastal areas of Korea. 4,10,11 Thus, feeding virus-infected wild marine fish to domestic stock is considered to be a potential route of viral infection. 23,25 A survey of fish viruses from wild marine fishes in coastal areas can provide significant information.…”
mentioning
confidence: 99%
“…However, several pathogenic fish viruses have been isolated or detected from wild marine fish in coastal areas of Korea. 4,10,11 Thus, feeding virus-infected wild marine fish to domestic stock is considered to be a potential route of viral infection. 23,25 A survey of fish viruses from wild marine fishes in coastal areas can provide significant information.…”
mentioning
confidence: 99%
“…In Far East Asia, VHSV was first isolated from free-living olive flounder Paralichthys olivaceus in 1999 (Takano et al, 2000). Since then, VHSV-infection with severe mortality has occurred frequently at olive flounder farms in Korea and Japan (Isshiki et al, 2001;Kim et al, 2009) and VHSV has isolated from several wild marine fish species obtained on both Korean and Japanese coasts (Watanabe et al, 2002;Kim et al, 2011a).…”
Section: Viral Hemorrhagic Septicaemia (Vhs) Is An Infectiousmentioning
confidence: 99%
“…VHSV is a member of the genus Novirhabdovirus from the family Rhabdoviridae (Trdo et al, 2005), and classified into four genotypes I-IV (Benmansour et al, 1997;Stone et al, 1997;Nishizawa et al, 2002;EinerJensen et al, 2004;Elsayed et al, 2006;Gagné et al, 2007;Kim et al, 2011a So far, VHSV has not been isolated and/or detected from salmonids including rainbow trout in Korea, and mariculture for rainbow trout and masu salmon O. masou has been initiated on the Korean coast near olive flounder farms. Although it was previously reported that Asian VHSV isolates from olive flounder were pathogenic to rainbow trout fry (Kim et al, 2011b), pathogenicity of VHSV to masu salmon is remained unclear.…”
Section: Viral Hemorrhagic Septicaemia (Vhs) Is An Infectiousmentioning
confidence: 99%
“…As olive flounder ( Paralichthys olivaceus ) is one of the preferred food sources in Korea, there has been an increase in the number of olive flounder farms. However, many farms have suffered substantial financial loss due to the occurrence of viral hemorrhagic disease (VHS) [1,2,3]. …”
Section: Introductionmentioning
confidence: 99%